2002
DOI: 10.1108/09574090210806469
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Sourcing Practices and Relationships

Abstract: Product‐sourcing practices can impact the competitiveness of an organization's products and services. Many sourcing practices exist and the challenge is to find the right practice, for the right product, at the right time. This paper describes a survey of 3,500 of UK companies, and reports on current and intended manufacturing sourcing practices; the associated decision‐making processes; and, the principal motives behind sourcing decisions. Key findings demonstrate a strong and ambitious trend towards open, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Leading up to the research presented in this paper, our previous work has investigated the principles on which manufacturers should form their strategic positioning decision. This was based on survey‐ and case‐based research as reported in Baines and Kay (2002) and Philpott et al (2004). This earlier research revealed three key principles that leading manufacturers apply when making these decisions.…”
Section: Background and Previous Researchmentioning
confidence: 99%
“…Leading up to the research presented in this paper, our previous work has investigated the principles on which manufacturers should form their strategic positioning decision. This was based on survey‐ and case‐based research as reported in Baines and Kay (2002) and Philpott et al (2004). This earlier research revealed three key principles that leading manufacturers apply when making these decisions.…”
Section: Background and Previous Researchmentioning
confidence: 99%
“…[34], Fraering and Prasad [35], Nellore et. al [36], Kotabe and Murray [37]; manufacturing sourcing practices by Narashimhan and Das [38], and Baines and Kay [39]. Various researchers proposed the supplier selection methods in several ways including Nydick and Ronald [40], Weber and Ellram [41], Chao et al [42], Masella and Rangone [43], Sarkis and Talluri [44], Barla [45], Dulmin and Mininno [46], and Humphreys et al [47].…”
Section: Strategic Positioning Decision Making Processesmentioning
confidence: 99%
“…Probert described the development and use of a systematic approach to formulating a make or buy strategy. Research on strategic sourcing covered by writers includes Greaver (1999), Quinn and Hilmer (1994), Lonsdale and Cox (1998), Tayles and Drury (2001), Jennings (2002), Barragan et al (2003), Freytag and Kirk (2003), Jin (2004) and Talluri and Narasimhan (2004); partnerships and relationships by Lamming (1993) and Macbeth and Ferguson (1994); global sourcing by Narasimhan and Carter (1990), Cavusgil et al (1993), Fraering and Prasad (1999), Nellore et al (2001), Kotabe and Murray (2004); manufacturing sourcing practices by Narasimhan and Das (2000) and Baines and Kay (2002). Various researchers proposed the supplier selection methods in several ways including Nydick and Hill (1992), Weber and Ellram (1993), Chao et al (1993), Masella and Rangone (2000), Sarkis and Talluri (2002), Barla (2003), Dulmin and Mininno (2003) and Humphreys et al (2003).…”
Section: Strategic Positioning Decision Making Processesmentioning
confidence: 99%